Elementary concepts of power electronic drives - Sundareswaran, K. (Kinattingal), 1966- (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
''Elementary Concepts of Power Electronic Drives' aims to facilitate a smooth transition from basic knowledge of electric machines and power electronics to the world of power electronics. The proposed book emphasizes only on relevant principles of electric motors and power electronics and then integrates such facts to bring the principle power electronic control of electric motors. Salient features of motors and power converter operations are crisply mentioned at appropriate places. Different case studies and solved numerical examples are provided in large numbers including illustrations through commonly seen electric drives'--
Components of power electronics drives -- Analysis of power electronic circuits -- AC-DC converters -- Motor modeling and control aspects -- AC-DC converter fed DC motor drives -- DC-DC converter -- Motor speed control employing DC-DC converters -- AC to AC converters -- Induction motor fundamentals -- Induction motor speed control using AC-AC converters -- DC-AC converters -- Speed control of induction motors and synchronous motors.
Keywords: Power electronics; Electric current converters; Switching power supplies